1 - Technology Transfer, Foreign Direct Investment and Economic Growth in Nigeria - Awosusi, Omojola Omowumi; Awolusi, Olawumi Dele (Africa Development, 2021)
The aim of this study is to investigate the long-run equilibrium relationship between various international factors and economic growth, as well as to assess the short-term impact of inward FDI, trade and economic growth on international technology transfer to Nigeria. To achieve this, the study used a time series data from 1970 to 2010. A multivariate co-integration technique developed by Johansen and Juselius (1990) was employed to investigate the long-run equilibrium relationships between the international factors and economic growth. The results of the analysis affirmed the existence of co-integrating vectors in the systems of this country during the study period (Lee and Tan 2006). The short-term impact of inward FDI, trade and economic growth on international technology transfer to Nigeria was also tested via Granger Causality test, based on Vector Error-Correction Model. The results of the test revealed a short-run causal effect either running unidirectionally or bidirectionally among the variables for the country. Policy implications are highlighted at the end of this article.